2015
DOI: 10.1080/2162402x.2015.1095433
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine enhances antitumor efficacy of recombinant lipoimmunogen-based immunotherapy

Abstract: Although immunotherapy is an attractive approach for cancer treatment, increasing evidence has shown that the combination of immunotherapy with other treatment modalities may improve the outcome of advanced malignancy. We combined the anticancer drug gemcitabine (Gem) with recombinant lipoprotein-based immunotherapy (rlipo-E7m/CpG) to treat advanced cancer. Mice bearing huge solid tumors (3 12 mm in diameter) or orthotopic cervical cancer were treated with a therapeutic regimen consisting of rlipo-E7m/CpG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, cyclophosphamide showed the ability to deplete the frequency and/or immunosuppressive capacity of regulatory T cells (Tregs), thereby enhancing immune effector cell-mediated antitumor responses [ 9 ]. Similarly, gemcitabine, oxaliplatin and paclitaxel were reported to reduce the tumor infiltration of myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) and/or Tregs [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cyclophosphamide showed the ability to deplete the frequency and/or immunosuppressive capacity of regulatory T cells (Tregs), thereby enhancing immune effector cell-mediated antitumor responses [ 9 ]. Similarly, gemcitabine, oxaliplatin and paclitaxel were reported to reduce the tumor infiltration of myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) and/or Tregs [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, such effects were detected only with repeated administration of Gem at high doses or with concomitant administration of additional adjuvants. 36,37 Importantly, previous studies have demonstrated that administration of multiple doses of Gem suppresses CTL responses in mice transplanted with TC-1 cells, with a reduction in antitumour effectiveness. 37 In contrast, in our preclinical test, mice treated with two doses of Gem or with Gem + pgDE7h showed no signs of morbidity, weight loss, or a reduction in the number of circulating CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Previous evidence has also demonstrated that Gem combined with immunotherapies blocks immunosuppressive mechanisms by reducing the levels of PD-1-expressing cells, MDSCs, tumor-infiltrating Tregs, and tumor-associated macrophages (TAMs). 36,42 The inhibitory effects of Gem on these cells may contribute to the tumor protection observed in mice subjected to combination therapy based on pgDE7h. Indeed, our own previous observations clearly demonstrated that the combination of active immunotherapies with blockade of immunosuppressive mechanisms, such as neutralization of IL-10, inhibition of IDO, or depletion of MDSCs, 23,24,43,44 represents a trend toward the development of treatments capable of controlling HPV-associated tumors, particularly at advanced growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…was able to control the growth of a syngeneic pancreatic tumor model, particularly when combined with gemcitabine (an antimetabolite used as standard of care for pancreatic cancer patients). [248][249][250][251] LOAd703 infection was associated with DC maturation/activation which in turn increased the activation/expansion of NK and tumor-specific T cells. Following on these encouraging preclinical data, the safety and oncolytic viro-immunotherapeutic efficacy of LOAd703 will be investigated clinically against pancreatic malignancy (for details, see "Recently initiated clinical trials" below).…”
Section: Preclinical and Translational Advancesmentioning
confidence: 99%